Analisa Efektivitas Penyaluran Zakat BAZNAS Kabupaten Kudus - Nafi', Muhammad Agus Yusrun (ZISWAF, 2020)
The National Zakat Agency (BAZNAS) Kudus Regency is a non-structural government institution that manages zakat in the Kudus Regency area. The problem in this research is how the effectiveness of zakat distribution of BAZNAS in Kudus Regency? The objectives of this study include: to measure the effectiveness of zakat distribution for BAZNAS in Kudus Regency. This research uses qualitative and quantitative methods. The qualitative method uses a descriptive approach. Meanwhile, the quantitative method uses the Zakat Core Principle ratio (ZCP) measurement model. The object used in this study is the BAZNAS financial statements in the first year of 2019. The results of this study indicate that the amount of Zakat collection in 2019 Rp. 2,682,855,379. Meanwhile, the amount of Zakat distribution in 2019 was Rp. 1,856,423,965 Based on the ZCP, the level of effectiveness of distribution in 2019 was operating at 70% (seventy percent). This shows that the level of effectiveness of BAZNAS zakat distribution in 2019 is in the Effective category where the Allocation to Collection Ratio (ACR) reaches 70 percent - 89 percent.